Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1007/s004200050422
|View full text |Cite
|
Sign up to set email alerts
|

Exposure assessment and sensitisation in workers exposed to organic acid anhydrides

Abstract: The data showed that biological monitoring is a useful tool in the exposure assessment of OAAs. Comparing the prevalence of sensitisation and the results of biological monitoring, between the three plants, we found that sensitisation increased with increasing exposure. Within a plant a higher risk of sensitisation in persons working in highly exposed areas at the time of the examination could not be seen, possibly due to frequent job rotation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
(17 reference statements)
1
6
1
Order By: Relevance
“…The levels were probably not higher before the study. The exposure levels, as well as the prevalences of sensitization and work-related symptoms, were lower than found in an earlier study of workers exposed to HHPA (7), but similar to those found in other factories, where the exposure was comparable (8)(9)(10).…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…The levels were probably not higher before the study. The exposure levels, as well as the prevalences of sensitization and work-related symptoms, were lower than found in an earlier study of workers exposed to HHPA (7), but similar to those found in other factories, where the exposure was comparable (8)(9)(10).…”
Section: Discussioncontrasting
confidence: 40%
“…Different OAA have varying sensitizing potentials (3,5,6). In particular, HHPA causes high frequencies of symptoms (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Other studies such as that reported by Drexler et al (2000) found an association between the acquisition of sensitisation and increasing levels of exposure to MTHPA, while Rosqvist et al (2003) reported that cases with specific IgE antibody, consistent with the acquisition of sensitization, increased with increasing exposures to MTHPA.…”
Section: Acid Anhydridesmentioning
confidence: 87%
“…Dose-response relationships in the development of sensitisation to acid anhydrides have been described, but it has not been possible to define clear thresholds Nielsen et al, 2001;Drexler et al, 2000;Rosqvist et al, 2003). In a prospective study reported by Welinder et al (2001), serum IgE antibody was found in 13% of workers exposed to several acid anhydrides (HHPA, MHPA, and MTPHA) with a mean combined exposure level of 15.4 mg/m 3 (range <1-189 mg/m 3 ).…”
Section: Acid Anhydridesmentioning
confidence: 93%
“…acid anhydrides, whereas for others, the results have been less promising [9]. It has been shown that increased exposure to anhydrides results in increased sensitization rates [10], and the development of IgE antibodies to anhydride-HSA conjugates can be predictive for later development of anhydride-induced respiratory disease [11]. Although the sensitivity of in vitro testing for both present and prospective asthma was reported to be high [11], subjects with work-related complaints but negative in vitro testing have been described [3, 11, 12].…”
Section: Discussionmentioning
confidence: 99%